2011
DOI: 10.1590/s0103-64402011000600002
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological study of radicular cysts diagnosed in a Brazilian population

Abstract: The aim of this study was to investigate the histopathological features of radicular cysts (RCs) diagnosed in a Brazilian population. Seventy-three cases of RCs, from a total of 1480 biopsies diagnosed between 2001 and 2008 at the Laboratory of Oral Surgical Pathology of the Dental School of the Federal University of Bahia were investigated regarding their histopathological features. Morphological results showed that exocytosis (n=50), spongiosis (n=40), acanthosis (n=28), atrophic epithelium (n=27) and apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 23 publications
3
14
2
3
Order By: Relevance
“…The presence of plasma cells in cysts suggests a local humoral immune reaction, and indicates that the majority of the lesions were in a developing stage. 6 Another histopathological feature evaluated was the presence of cholesterol crystals, which were observed in 13.6% of periapical cysts, a rate similar to that found by Santos et al 16 The major source of cholesterol may be from locally dying inflammatory cells, and a result of the disintegrating membranes of these cells in long-standing lesions. 17 Accumulation of cholesterol crystals can prevent healing in apical periodontitis lesions, 17 but this accumulation does not seem to be associated with the maintenance of periapical cysts inasmuch as the frequency of its occurrence is low in these lesions.…”
Section: Resultssupporting
confidence: 55%
“…The presence of plasma cells in cysts suggests a local humoral immune reaction, and indicates that the majority of the lesions were in a developing stage. 6 Another histopathological feature evaluated was the presence of cholesterol crystals, which were observed in 13.6% of periapical cysts, a rate similar to that found by Santos et al 16 The major source of cholesterol may be from locally dying inflammatory cells, and a result of the disintegrating membranes of these cells in long-standing lesions. 17 Accumulation of cholesterol crystals can prevent healing in apical periodontitis lesions, 17 but this accumulation does not seem to be associated with the maintenance of periapical cysts inasmuch as the frequency of its occurrence is low in these lesions.…”
Section: Resultssupporting
confidence: 55%
“…This study showed that the average size of radicular cysts with Actinomyces colonization was 1.78 cm, which is similar to the value reported by a previous study (24) in which the average size of these cysts was nearly 2.0 cm. When this result was compared with those previously described by Kukiane et al (23), although that study used a method different from the one applied in the present study, the presence of Actinomyces did not appear to increase the size of the radicular cyst lesions.…”
Section: Discussionsupporting
confidence: 91%
“…Histopathologically, all cases fulfilled the criteria for a radicular cyst (24), but all cases were associated with an Actinomyces infection. These colonies were present in the lumen or adjacent to the cyst, had different sizes, were isolated or sometimes overlapping, and were characterized by filamentous structures radiating from the center that were positive on PAS and Grocott staining and surrounded by an inflammatory infiltrate.…”
Section: Discussionmentioning
confidence: 94%
“…Radicular cyst accounted for 12.6% of all the lesions in the present study, which was much higher than the data of Santos et al . (4.9%), reported in a Brazilian population of all ages. Additionally, radicular cyst was the most common lesion in the odontogenic cyst group (80%) in this study and was predominantly greater than the other lesions within this group; this result was similar to the data of other studies.…”
Section: Discussionmentioning
confidence: 83%